La coordinación visomotora y su incidencia en la lecto-escritura en los niños y niñas de primer año de preparatoria de educación general básica de la unidad educativa Marco Aurelio Subía Martínez – batalla de Panupali en el año lectivo 2013-2014 - Chancusig Quinatoa, Liliana Maricela (2015)
This research work was initiated with the aim of creating a manual with activities for beginning reading - writing considering that visuomotor coordination assistance in the development of learning allowing adequate development for children to acquire education adequate and can navigate the educational environment .The Manual consisted of scientific content which allowed new knowledge to teachers, plus graphic expression exercises that improve the spelling of children / as in First Year of School of Basic Education General, through inquiry of technical and scientific contents that allow design strategies to define the scope of action of the theory in the development of graphic expression and initiation to writing, so that aspects that should be favored in the initiation….